Radiation Therapy Care During a Major Outbreak of COVID-19 in Wuhan - Wu, Shen (Adv Radiat Oncol, 2020)
PURPOSE: The epidemic of coronavirus disease 2019 (COVID-19) challenges the prevention and protection of the cancer patients and the staff in the department of radiation oncology. METHODS: At the Hubei Cancer Hospital, we organized an emergency infection control team to lead special efforts to combat COVID-19 during this challenging time. RESULTS: Radiation therapy treatments were resumed on January 30th and have never stopped again at the hospital regardless of the circumstances of the ongoing outbreak. Between January 30th and the time of the writing, we have treated over 100 radiation therapy patients, with no incidence of on-site COVID-19 transmission between patients and health care workers in the duration. CONCLUSIONS: Our experience will help guide the practice in other regions that are or might be facing outbreaks of this disease.